The importance of private international law in the modern world - Delgado Menéndez, María Antonieta (2024)
This paper addresses the importance of Private International Law (hereinafter, PIL) in the modern world marked by an increasing human cosmopolitanism, the intensification of free trade of goods, services and capital, and by an avalanche of legal relationships, which daily cross the borders of states, greatly increasing international legal traffic. International private relations, being linked to a multiplicity of countries and state legal systems, give rise to a kind of legal uncertainty as to the law applicable to them, which must be clarified by private international law in order to provide legal certainty to the parties.In this context, the authors offer a look at two essential problems. The first is a cross-cutting issue in private international law, which is part of its general provisions: fraud in private international law, a little known mechanism in the Peruvian legal community, although highly relevant in the determination of the law applicable to international private relations. The second is a fundamental issue for international families and for third parties related to them, which deals with the patrimonial effects of international marriages and de facto unions; an issue that has been one of the most frequent and complex in matters of conflict of laws in private international law and that is undergoing a very important evolution in the modern world of the 21st century.